2020
DOI: 10.1093/aobpla/plaa009
|View full text |Cite
|
Sign up to set email alerts
|

The importance of quantitative trait differentiation in restoration: landscape heterogeneity and functional traits inform seed transfer guidelines

Abstract: For widely distributed species, understanding the scale over which genetic variation correlates to landscape structure and composition is critical. Particularly within the context of restoration, the evolution of genetic differences may impact success if seeds are maladapted to the restoration environment. In this study, we used Geum triflorum to quantify the scale over which genetic differences for quantitative traits important to adaptation have evolved, comparing the proportion of variance attributed to bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 61 publications
0
49
0
Order By: Relevance
“…Varying genomic composition of commercial seed sources relative to wild, contemporary populations suggest further study is required to evaluate whether genomic differences correspond to functional differences that impact restoration success. Common garden studies have shown that seed transfer across environments can impact plant traits and performance (Bucharova et al 2017, Giencke et al 2018, Johnson et al 2004, Lesica & Allendorf 1999, Yoko et al 2020). Consequently, the genomic differences we observe here warrant additional study of H. maximiliani seed sources linking genomic differences to traits important to adaptation and persistence in restored environments.…”
Section: Discussionmentioning
confidence: 99%
“…Varying genomic composition of commercial seed sources relative to wild, contemporary populations suggest further study is required to evaluate whether genomic differences correspond to functional differences that impact restoration success. Common garden studies have shown that seed transfer across environments can impact plant traits and performance (Bucharova et al 2017, Giencke et al 2018, Johnson et al 2004, Lesica & Allendorf 1999, Yoko et al 2020). Consequently, the genomic differences we observe here warrant additional study of H. maximiliani seed sources linking genomic differences to traits important to adaptation and persistence in restored environments.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is not often practical, since in the frame of germplasm collecting, extensive genetic characterization may lead to redundancy (Jaramillo and Baena 2000, Parra‐Quijano 2011), and resources for this task are a limiting factor (Vogel et al 2005). However, validation of the delineated STZs in terms of genetic differentiation is essential (Massatti et al 2020, Yoko et al 2020) especially in the context of climate change. Here we present provisional spatiotemporal STZs as a first step in seed transfer guidance for restoration purposes of Argentinian rangelands in response to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study in hihi (Notiomystis cincta ) used pedigree-based heritability to reveal low evolutionary potential in this threatened bird (de Villemereuil et al, 2019a). In addition to heritability, known family groups or distinct populations have also been essential to understanding GxE interactions, especially in plant species (Bisbing et al, 2020;Yoko, Volk, Dochtermann, & Hamilton, 2020). Empirical estimates of relatedness can be used instead of pedigrees, and may overcome pedigree pitfalls while providing realised estimates of genome-sharing (Hill & Weir, 2011;Hill & Weir 2012;Speed & Balding, 2015).…”
Section: Pedigrees and Quantitative Geneticsmentioning
confidence: 99%